Distributed primal–dual interior-point methods for solving tree-structured coupled convex problems using message-passing. (4th May 2017) - Khoshfetrat Pakazad, Sina; Hansson, Anders; Andersen, Martin S.; Nielsen, Isak
Abstract : In this paper, we propose a distributed algorithm for solving coupled problems with chordal sparsity or an inherent tree structure which relies on primal–dual interior-point methods. We achieve this by distributing the computations at each iteration, using message-passing. In comparison to existing distributed algorithms for solving such problems, this algorithm requires far fewer iterations to converge to a solution with high accuracy. Furthermore, it is possible to compute an upper-bound for the number of required iterations which, unlike existing methods, only depends on the coupling structure in the problem. We illustrate the performance of our proposed method using a set of numerical examples.